2023
DOI: 10.3390/jcs7060248
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and Mechanical Properties of Recyclable Composites Prepared from Bio-Olefins and Industrial Waste

Perla Y. Sauceda-Oloño,
Ana C. Borbon-Almada,
Martin Gaxiola
et al.

Abstract: Ordinary Portland Cement (OPC) production consumes tremendous amounts of fresh water and energy and releases vast quantities of CO2 into the atmosphere. Not only would an alternative to OPC whose production requires no water, releases little CO2, and consumes less energy represent a transformative advance in the pursuit of industrial decarbonization, but the greater availability of safe drinking water would lead to significantly improved public health, particularly among vulnerable populations most at risk fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 75 publications
1
9
0
Order By: Relevance
“…Samples that were remelted several (at least six) times (at 160°C) exhibited properties identical to those made by remelting the initial reaction products, emphasizing the facile thermal recyclability of the materials. Similar recyclability without diminishing mechanical strength has been reported for several other HSMs comprising ≥80 wt% sulfur 61–64 …”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Samples that were remelted several (at least six) times (at 160°C) exhibited properties identical to those made by remelting the initial reaction products, emphasizing the facile thermal recyclability of the materials. Similar recyclability without diminishing mechanical strength has been reported for several other HSMs comprising ≥80 wt% sulfur 61–64 …”
Section: Resultssupporting
confidence: 83%
“…Similar recyclability without diminishing mechanical strength has been reported for several other HSMs comprising ≥80 wt % sulfur. [61][62][63][64] SEM with elemental mapping by energy-dispersive x-ray analysis (SEM-EDX) showed that GBS 80 and GBS 90 had uniform distributions of carbon, oxygen, and sulfur (Figure 6) and provided evidence of the successful homogenization of the PGB comonomer during the inverse vulcanization reaction.…”
Section: Synthesis and Chemical Characterization Of Compositesmentioning
confidence: 99%
“…Traditional materials such as the bricks and mineralbased tiles discussed above significantly deteriorate due to water absorption or exposure to acidic condition, whereas previous HSMs have shown remarkable resistance to water absorption or mechanical strength degradation after exposure to acid. 97,98 CPS and GPS were likewise found to exhibit <1 wt% water uptake after soaking in water for 24 h (compared to up to 28% for mineral products like Portland cement). CPS and GPS were also evaluated for resistance to acid degradation by submerging the materials in 0.5 M sulfuric acid for 24 h. After this exposure, CPS retained 64% and GPS retained 80% of their compressive strengths.…”
Section: Composite Thermal and Mechanical Propertiesmentioning
confidence: 96%
“…Cylinders appropriate for compressive strength analysis (Figure 1) were prepared by filling a silicone mold with finely powdered composite and heating the material in the mold in a 160 C oven for 2 h. Once shaped, the samples were allowed to sit at room temperature in the dark for 96 h before testing, following the procedure used for most other HSMs for which compressive strength data are reported. 26,[42][43][44] The compressive strength of SPC 90 was 12.8 ± 1.6 MPa (Table 2; stress-strain plots provided in Figure S5). Whereas SPC 90 exhibits a lower compressive strength (12.8 MPa) than SPG (23.1 MPa) 26 or BC 90 (22.5 MPa), 28 the compressive strength of SPC 90 is competitive with common commercial structural materials like bricks (classification C62) used in retaining walls and other non-load bearing applications.…”
Section: Mechanical Properties Of Composite Spc 90mentioning
confidence: 99%